50 let soudního inženýrství na Vysokém učení technickém v Brně - Bradáč, Albert (Akademické nakladatelství CERM, 2015)
V rámci 50. výročí oboru soudní inženýrství a 45 let Ústavu soudního inženýrství na Vysokém učení technickém v Brně je v příspěvku krátce shrnuta jeho historie.

In the framework of the 50th anniversary of forensic engineering and 45 years of the Institute of Forensic Engineering at Brno University of Technology in the paper briefly summarized its history.
50 Years of Forensic Engineering at Brno University of Technology
Keywords: znalec; soudní inženýrství; výchova znalců; certifikace expertů; Ústav soudního inženýrství; Vysoké učení technické v Brně; expert; forensic engineering; education of experts; certification of experts; Institute of Forensic Engineering; Brno University of Technology